2020
DOI: 10.1002/pits.22350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of developmental relationships with teachers on middle‐school students’ motivation and performance

Abstract: We examined how middle‐school students’ motivation, belonging, school climate, and grade point average (GPA) are affected by students experiencing developmental relationships—those that go beyond teachers being caring (e.g., showing warmth to students) and providing challenge (e.g., high expectations) to also include teachers providing support, sharing power, and expanding students’ sense of possibilities. We also examined variations in those associations by student socioeconomic status (SES). The study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 75 publications
(128 reference statements)
3
39
0
Order By: Relevance
“…The effects on GPA were, as expected, considerably smaller, with Time 1 GPA by far the most powerful predictor of end of the year GPA. In another study, we found that the effects of developmental relationships on GPA are significant, but largely indirect, through the effect that those developmental relationships have on student's motivation (Scales et al, 2018).…”
Section: Meaningfulness Of the Effects Of Developmental Relationshipsmentioning
confidence: 83%
See 1 more Smart Citation
“…The effects on GPA were, as expected, considerably smaller, with Time 1 GPA by far the most powerful predictor of end of the year GPA. In another study, we found that the effects of developmental relationships on GPA are significant, but largely indirect, through the effect that those developmental relationships have on student's motivation (Scales et al, 2018).…”
Section: Meaningfulness Of the Effects Of Developmental Relationshipsmentioning
confidence: 83%
“…When these five relational elements are experienced, students tend to report more favorable scores on a variety of psychological, social-emotional, behavioral, and academic indicators (Pekel et al, 2015; Pekel et al, 2018; Scales et al, 2018). For example, in a study of nine middle and high schools that looked at elements related to expressing care, challenging growth, and sharing power, students who reported having high levels of these strategies in their schools were 130% to 222% more likely than their peers to feel a sense of belongingness to school, and 53% to 61% more likely to feel academically confident and capable (Scales & Benson, 2007; Scales, 2013).…”
Section: Student-teacher Developmental Relationshipsmentioning
confidence: 99%
“…This paper reports on a longitudinal study of student–teacher relationships and motivation, focusing on the perspective of teachers. The larger study (see details in Scales et al, 2020 and Scales et al, 2019) involved more than 1500 middle and high school students and nearly 200 teachers over two school years and included quantitative student and teacher surveys, student focus groups and teacher interviews at the beginning and end of one school year, and at the beginning of the second school year. The intent of the study was to examine how the quality of student–teacher developmental relationships affects students’ academic motivation, connectedness to school, perceptions of the quality of curriculum and performance (grades and test scores).…”
Section: Methodsmentioning
confidence: 99%
“…Thijs and Fleischmann (2015) observed that students who reported high levels of closeness with their teachers tended to also exhibit higher levels of mastery goal orientation than their peers, promoting higher achievement. In addition, when the quality of a student’s relationship with their teacher increases over the academic year, students also demonstrate increases in their academic motivation and perceptions of belongingness (Martin and Dowson, 2009; Scales et al, 2019, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Over the years many studies [14,15,16,17] have been done to investigate the effects of motivation on teachers' performance and their retention. Though this has somehow aided in the improvement of performances in some schools, however, the level of attrition is still high.…”
Section: Original Research Articlementioning
confidence: 99%